Analysis Of Perceived Value of Benefit Cash on Delivery Payment Method Customers When Using Digital Wallet Application - Serius Nazara, Desman; Ratnawita; Ekasari, Silvia; Sulistiarini, Emma Budi; Yuniarti Utami, Eva (SEULANGA SYSTEM PUBLISHER, 2024)
The purpose of this study is to examine how secure and comfortable cash on delivery (COD) and e-wallet consumers feel about their payment options. Survey research is the method employed in this study. All students are the population in question. Purposive sampling was the method of sampling that was applied. 100 people made up the sample in this study. In order to collect data for this study, questionnaires, records, and interviews were used. Quantitative data analysis is the method employed. Two associated samples are compared in this study using a comparative analysis sample type. The study's conclusions revealed that consumers' comfort levels with cash-on-delivery and e-wallet payment options differ. Convenience with cash on delivery is valued at 48.5 on average, whereas e-wallet convenience is valued at 58.5. Consequently, it can be said that the e-wallet payment method offers more convenience than the cash on delivery payment option. Users of e-wallet payment options and cash on delivery have different levels of security. For COD security, the average value is 37.5, and for e-wallet security, it is 39.5. It is evident that there is little difference in the average value of cash on delivery security (2.5) between it and e-wallet security. Even so, the security level of e-wallets is higher than the security of cash on delivery (COD).